The Psychometric Properties of the Simple Screening Instrument for Substance Abuse. (December 2015) - Boothroyd, Roger A.; Peters, Roger H.; Armstrong, Mary I.; Rynearson-Moody, Sarah; Caudy, Michael
The Simple Screening Instrument for Substance Abuse (SSI-SA) is gaining widespread use as a self-report measure of substance abuse; yet, little information exists regarding the instrument's psychometric properties. This study examined the SSI's psychometric properties within a population of 6, 664 adult Medicaid enrollees in Florida, who responded to a survey conducted as part of a statewide evaluation of Medicaid services. The SSI-SA had excellent internal consistency (.85). Evidence of the SSI's validity was strong; SSI-SA scores distinguished among individuals with and without substance abuse needs and were significantly correlated with a measure of functioning in daily living. Using the recommended SSI-SA cutoff score of 4 or higher to indicate the presence of a substance abuse problem, the SSI-SA had respectable sensitivity (.82) and specificity (.90).